A182 HEPATOCELLULAR CARCINOMA (HCC) SCREENING PRACTICES IN CHRONIC HEPATITIS B (HBV) AMONG CANADIAN GASTROENTEROLOGISTS AND HEPATOLOGISTS: AN ONLINE SURVEY. (1st March 2018) - Yau, A; Galorport, C; Ko, H; Coffin, C S
Abstract: Background: Current guidelines recommend HCC surveillance in certain chronic HBV carriers: Asian male age > 40, Asian female age > 50, African/Non-African blacks, family history of HCC and cirrhosis. Aims: To determine the HCC screening practices among Canadian gastroenterologists and hepatologists. Methods: An online survey was performed. Results: At this point, 22 responded (5 hepatologists, 17 gastroenterologists) and their years in practice were: < 5 (18.2%), 6–10 (22.7%), 11–15 (13.6%), 16–20 (4.5%), and > 21 (40.9%). The number of HBV patients seen per year was: < 10 (31.8%), 10–100 (36.4%), 100–200 (18.2%), 200–500 (4.5%), and > 500 (9.1%). All hepatologists and 12 (70.6%) gastroenterologists treat HBV. 77.3% (17/22) order US about every 6 months at the time of clinic visits, while 13.6% (3/22) have an automatic recall system and 9.1% (2/22) refer back to primary care physicians. 54.5% (12/22) include alpha-fetoprotein (AFP) with ultrasound. For non-Asian, non-African HBV patients, 36.4% (8/22) screen them the same way as in Asians, 31.8% (7/22) screen with US every 6 months starting at an older age, 13.6% (3/22) screen with annual US at the same age, 9.1% (2/22) screen with annual US at an older age, and 9.1% (2/22) screen only cirrhotic. For young (age < 40) non-African HBV patients with a family history of HCC, 36.4% (8/22) screen with US every 6 months regardless of age, 27.3% (6/22) screen with US and AFP every 6 months regardless of age, 18.2% (4/22) screen with annual US regardless of age, and 18.2% (4/22) screen the same way as those without a family history. For HBV patients with non-alcoholic fatty liver disease (NAFLD): 50% (11/22) screen the same way as those without NAFLD, 31.8% (7/22) start screening with US every 6 months regardless of age if advanced liver fibrosis (≥F3) is present, 9.1% (2/22) screen with MRI every 6 months regardless of age if advanced fibrosis (≥F3) is present, and 9.1% (2/22) screen with US every 6 months regardless of age and stage of fibrosis. Obstacles to HCC screening reported: lack of an automatic recall system (54.5%; 12), patient non-compliance (31.8%; 7), and limited access to US/MRI (13.6%; 3). Conclusions: HCC screening practice vary widely among gastroenterologists and hepatologists for HBV patients with non-Asian, non-African descent, family history of HCC, and NAFLD. Incidence of HCC in these populations is unknown and HCC screening guidelines are desperately needed for these patients. Implementation of an automatic recall system could potentially facilitate HCC screening. Funding Agencies: None